Standardization of phototherapy for neonatal hyperbilirubinemia using multiple-wavelength irradiance integration - Shin Kato; Osuke Iwata; Yasumasa Yamada; Hiroki Kakita; Takaharu Yamada; Hideyuki Nakashima; Tokio Sugiura; Satoshi Suzuki; Hajime Togari (Pediatrics and Neonatology)
Background: Phototherapy with radiation of 460–490 nm wavelengths provides the most potent therapeutic effect for neonatal jaundice. However, the efficacy of phototherapy has been estimated using single-wavelength detectors with sensitivity at approximately 460 nm. Cyclobilirubin formation capacity (CFC), which comprises the sum of the irradiance values from three wavelengths multiplied by their specific coefficients, has been proposed as an alternative marker to evaluate the efficacy of phototherapy. This study aimed to test whether two types of phototherapy devices with distinct spectral characteristics provide similar therapeutic effects on adjustment of device-to-patient distances to deliver similar CFCs. Methods: Using a three-wavelength spectroradiometer, CFCs and footprints of the light-emitting diode and fluorescent tube devices were assessed. Having determined the device-specific distances that ensured similar CFCs, 32 newborn infants, requiring phototherapy for hyperbilirubinemia, were randomized into the light-emitting diode and fluorescent tube groups. The total serum bilirubin levels before and after phototherapy were assessed. Results: The light-emitting diode and fluorescent tube devices had comparable CFCs at distances of 60 and 50 cm, respectively. Phototherapy reduced the total serum bilirubin levels from 18.1 to 14.6 mg/dL and from 19.1 to 15.1 mg/dL in the light-emitting diode and fluorescent tube groups, respectively. The two groups did not differ significantly with respect to the patients' clinical backgrounds, serum bilirubin levels, or changes before and after phototherapy. Conclusion: At similar CFCs, the two phototherapy devices reduced the total serum bilirubin levels by comparable amounts. Hence, determining CFCs may help predict phototherapy efficacy. This may ensure better safety and greater efficacy of the treatment for newborn infants. Key Words: bilirubin, cyclobilirubin, irradiance, light-emitting diode, spectroradiometer